The Effect of Educational Games on Fine Motor Ability For Children Aged 4-5 Years in Kindergarten - Valenta Susfiandari; Miftakhul Jannah; Ruqoyah Fitri (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to know the influence of educational games on the abilities of children 4–5 years old in the garden.​​ Method: Design used in study This is a nonrandomized pretest-posttest control design where two groups are group experiments and group control with a quantitative approach. These research subjects are Child Group A at Al Falah Assalam Kindergarten, which has as many as 26 students as class experiments, and Children Group A at Kindergarten Al Falah Darussalam, which has as many as 26 students as class control. Deep data analysis techniques use non-parametric statistics, such as the Mann-Whitney Test. Results: This research showed that educational games have influenced young children aged 4-5 years. This is known from the results of the posttest carried out in the control class, where the increase was not significant, like the results of the posttest carried out in the experimental class, which previously carried out treatment activities. Novelty: The novelty of this research is using educational games to play in real life so that young children can touch and feel. This educational game can be used to introduce not only letters but also numbers, shapes, and colors.